IMPACT OF BREAST CONSERVATION SURGERY VERSUS THE MODIFIED RADICAL MASTECTOMY ON THE QUALITY OF LIFE AMONG BREAST CANCER SURVIVORS IN PAKISTAN - Ahmed, Mumtaz; Mahmood, Namrah; Zaffar, Shaista; Rafique, Umbar; Ahmed, Moiz; Abbas, Kiran (Pakistan Armed Forces Medical Journal, 2020)
Objectives: To assess the quality of life (QoL) of patients receiving Breast conservation surgery as compared to the Modified Radical Mastectomy. Study Design: A case control study. Duration of Study: The study took place from August 2018 to September 30th 2019. Methodology: A prospective study using non probability sampling technique was conducted at Pakistan Institute of Medical Sciences. Quality of life was assessed using a QOL-CSV to evaluate the physical, psychological, social, spiritual well-being as well as distress and fear factors. Data was analyzed using SPSS software 20 and chi square test was applied. Results: Out of a total of 50 cases of BCS and 166 cases of modified radical mastectomy, mean age in breast conservation surgery group was 50.14± 4.8 and in the control group 54.7± 6.3. In case-group there were moderate score in physical, social, and psychological well-being as well as in fear factor and distress of diagnosis. No comparable difference was observed between case and control group with respect to physical, psychological, or spiritual wellbeing, distress score and fear factor. However significant difference was found in the quality of life regarding social concerns. Conclusion: Breast conservation surgery was associated with significant improvements in quality of life scores in terms of social and psychological well-being, with comparable physical and spiritual wellbeing in study population.